2011
DOI: 10.1111/j.1745-7599.2011.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental rights and decision making regarding vaccinations: Ethical dilemmas for the primary care provider

Abstract: Purpose: To discuss the ethical dilemma that a primary care nurse practitioner (NP) must face when parents refuse to have their children immunized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…They strived to stay in a neutral position when it came to informing the girls and their parents about the Swedish recommendations regarding HPV and the HPV vaccination. They said that they wanted to preserve the autonomy of the girls, and this meant that they did not want to influence or persuade them or give them personalized advice ( Fernbach, 2011 ). This created a dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…They strived to stay in a neutral position when it came to informing the girls and their parents about the Swedish recommendations regarding HPV and the HPV vaccination. They said that they wanted to preserve the autonomy of the girls, and this meant that they did not want to influence or persuade them or give them personalized advice ( Fernbach, 2011 ). This created a dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…A general mistrust of the government and pharmaceutical companies that approve and license vaccines may lead parents to have a higher level of trust in illegitimate sources, such as the stories of other parents (Smith & Marshall, 2010). Because the government monitors any adverse events that occur as a result of the administration of vaccines, parents may be skeptical as to whether the government is being honest when reporting any issues (Fernbach, 2011).…”
Section: Lack Of Trust In Health Care Providers and The Governmentmentioning
confidence: 98%
“…Certain vaccines have been questioned more than others within the religious community, particularly the HPV vaccine (Shelton, Snavely, Jesus, Othus, & Allen, 2013). This vaccine was the first created to prevent a specific type of cancer (Fernbach, 2011). According to the CDC, HPV is the most common sexually transmitted infection in the United States, affecting nearly all sexually active men and women at some point during their lifetime (CDC, 2014a).…”
Section: Religious Objectionsmentioning
confidence: 99%
“…Epidemiology data demonstrate that vaccine‐preventable diseases have been reduced and in some cases in the United States, completely eliminated. The challenge is that the parents of young children, as well as their younger healthcare providers, are no longer familiar with vaccine‐preventable diseases shifting fear from the disease to potential vaccine reactions (Epling et al., ; Fernbach, ; Salmon, Dudley, Glanz, & Omer, ). In a study by Martin and Badalyan (), 21% of specialty pediatricians and 9% of general pediatricians are found to deviate from the recommended Centers for Disease Control and Prevention (CDC) guidelines when considering vaccination for their future child citing safety concerns as their rationale.…”
Section: Introductionmentioning
confidence: 99%
“…With an ever‐changing immunization schedule and the addition of new vaccines, the total vaccines administered in a child's first 18 months of life, when everything is administered on time, are 25 inoculations (ODPHP, ). Fernbach () found that parents have a growing concern that an infant's immune system is too immature to respond correctly to such a large vaccine load. Fernbach went on to describe that this conclusion is not supported by research and that passive immunity acquired from the mother, through the development of B and T cells in utero combined with the innate neonatal immune response, does not result in an increased infection rate after immunization.…”
Section: Introductionmentioning
confidence: 99%